Sporangial viability and germination in Peronospora destructor - S.K. SUGHA, R.K. DEVELASH and (Indian Phytopathology, 2002)
Deionized water, pH 7.0, temp. range of 10-12 degC and RH _95% were opt. for sporangial germination and germ tube elongation of P. destructor. More sporangia harvested at 6.00 am germinated than those collected later in the day. Sporangia collected between 12.00 noon and 6.00 pm did not germinate. Dew drops collected from onion leaves enhanced sporangial germination and germ tube growth. Leaf extracts and leachates inhibited germination. Most of the sugars and amino acids tested stimulated sporangial germination. Washings of sporangia stimulated germination although repeated washings decreased germination drastically. Sporangia germinated better in darkness than in the light and yellow light inhibited germination. Wiped host surfaces supported better germination than unwiped surfaces. Viability of sporangia was higher in dew water compared with on detached leaves and in sporangial pellets. Viability of sporangia was reduced on exposure to sunlight.